Learning from the Mistakes: Time to Rebuild the WTO Dispute Settlement Mechanism - Bhat, Sandeep (Law and Policy Review, 2022)
Hailed as a “the jewel in the crown”, the WTO dispute settlement mechanism has been central in ensuring security and predictability to the rules of international trade. The WTO Appellate Body attained a central position in the dispensation of justice during the last two decades of its existence. Unfortunately, it has stopped functioning since December 10, 2019 due to the United States’ stance to block the appointment of its members. This stumbling block in the justice delivery system appeared at the worst possible time as the COVID-19 pandemic compelled the member states to adopt various means of trade protectionism in order to shield their domestic industry and to overcome economic losses suffered/sustained during the pandemic. The current trend across the globe leads to the obvious conclusion that the WTO obligations face the danger of subversion. With the increased trade barriers emerging out of the COVID-19 pandemic, more and more disputes are expected to reach the WTO Dispute Settlement Body (DSB). However, in the absence of the Appellate Body, serious questions arise regarding the efficacious dispensation of justice at the WTO level. Due to the lack of faith in WTO dispute settlement, member states may resort to take justice in their own hands and thereby end-up in a vicious circle of retaliatory measures. Such a situation is detrimental to the credibility of the WTO system. Hence, concerted efforts to restore the past glory of the WTO dispute settlement mechanism are indispensable and the current author is of the view that Asian states can take lead in this regard.